Study of feto-maternal outcome in patients with hepatitis E infection during pregnancy - Shah, Dipti M.; Prajapati, Prakash P.; Pandya, Munjal J.; Chaudhary, Nimisha J.; Dabhi, Gira C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hepatitis E is considered as a common cause of high maternal morbidity and mortality particularly in third trimester and also high perinatal morbidity and mortality. Thus, this study is conducted to evaluate the feto-maternal outcome in patients infected with hepatitis E during pregnancy. Methods: It is a retrospective observational study conducted in department of obstetrics and gynecology at L. G. hospital. Fifty pregnant women with clinical hepatitis in third trimester of pregnancy were included in this study and thorough investigation were carried out. Patients were monitored till postpartum period and fetal monitoring data were collected from neonatal ICU. Results: In this study, majority of pregnant patients with hepatitis B were admitted during monsoon season suggests that HEV outbreaks are more common during monsoon months. Majority of the patients (70%) were emergency cases. Majority of these patients (82%) were belonged to lower socio-economic class. Co-infection with HAV was in 2% and with HBV in 4%. S. bilirubin >15 mg/dl in 16% of patients. PT and APTT were raised in 28% of patients. FDP was raised in 70% of patients. 76% were delivered vaginally and 22% were delivered by LSCS. Most common complication in HEV infected pregnant women was disseminated intravascular coagulation (DIC) (26%). Maternal mortality rate is 14%. Out of 50 patients, 88% delivered live baby, out of which 72% needed NICU admission. Perinatal mortality rate was as high as 28%. Conclusions: Hepatitis E infection and pregnancy is a deadly and fatal combination. Specifically, in 3rd trimester of pregnancy, acute hepatitis E has a grave prognosis with high maternal morbidity and mortality. Prevention is the mainstay of controlling HEV especially in developing countries.